Teknik Klasifikasi C4.5 Dalam Menentukan Faktor Utama Kepuasan Nasabah Terhadap Pelayanan Klaim di PT Asuransi Central Asia Pematangsiantar - Syahputra, Muhammad; Windarto, Agus Perdana; Winanjaya, Riki (Bulletin of Data Science, 2021)
Insurance claims can be made in accordance with important provisions in claim submission, such as claims in accordance with those stated in the policy, the policy is still valid (inforce), the policy is not in the waiting period and the claim is included in the coverage. Data Mining is a computer-aided process to explore and analyze large amounts of data sets and extract information and knowledge. Decision Tree is one of the Data Mining sections, with C4.5 algorithm is one of the classification methods that use decision tree representations where each nodes present attributes, branches represent the values ​​of attributes, leaves represent classes. and can be used to find dominant factors to find a decision, one of which determines the main factors of customer satisfaction with service claims at PT. Insurance Central Asia Pematangsiantar. It is hoped that the results will later be able to contribute greatly to PT. Insurance Central Asia Pematangsiantar in providing the best service to existing customers